Ocena niepewności prognoz wyznaczanych na podstawie opinii eksperta - Gogolewska, Konstancja (Evaluation of the Forecasts Uncertainty, Based on the Expert's Opinion, 2006)
In many prognostic situations the complexity of the forecasted incident, the lack of required data from the past, as well as taking an active attitude toward the future requires the use of experts' opinion in the process of forecasting. In practice forecasting in a company, due to the low cost and the speed of achieving a forecast, often relies on a single judgement, formulated by a single expert.In this article we covered the problems relating to the evaluation of the level of uncertainty in point, variant and interval forecasts, based on expert opinion.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 59-68